Prevalence of Maternal Hypovitaminosis D and Obstetric Outcomes at Chonprathan Hospital, Nonthaburi, Thailand - Lersbuasin, Porntita; Ariyawatkul, Kansuda (Thai Journal of Obstetrics and Gynaecology, 2020)
Objective: The primary aim of this study was to determine the prevalence of maternal hypovitaminosis D. The secondary aim was to determine the obstetric outcomes between a group of pregnant women with hypovitaminosis D and the normal control group at Chonprathan Hospital, Nonthaburi province of Thailand. Materials and Methods: This study was a cross-sectional study. A total of 77 subjects were consecutively enrolled in the study. The inclusion criteria were pregnant women who had received antenatal care and delivered at Chonprathan Hospital, Nonthaburi, Thailand. The exclusion criteria included women who had a liver disease, kidney disease, gastrointestinal absorption disease, pulmonary tuberculosis, hyperthyroid disease, and pregnant women who used drugs that have an effect on vitamin D. Vitamin D deficiency was defined as 25-hydroxyvitamin D (25-OHD) < 20 ng/mL, insufficiency as 25-OHD 20–29.9 ng/mL, and sufficiency as 25-OHD > 30 ng/mL. Hypovitaminosis D refer to vitamin D deficiency plus vitamin D insufficiency. A data interview was performed and the results recorded in a case record form by the research team. Venous blood samples were collected for 25-OHD, parathyroid hormone (PTH), calcium, phosphate, alkaline phosphatase (ALP), albumin, and magnesium on the day of labor. Results: The mean level of 25-OHD was 25.2% ± 7.9 ng/mL. The prevalence of vitamin D deficiency was 22.1%, vitamin D insufficiency was 44.1%, and vitamin D sufficiency was 33.8%. There was an association between the vitamin D level and PTH and hematocrit, but no association between the other blood parameters statuses (correct calcium, phosphate, ALP, albumin, magnesium), age, pre-pregnancy body mass index, or obstetric complications. Conclusion: The prevalence of hypovitaminosis D was 66.2%, while vitamin D deficiency was 22.1%. There was no association between the vitamin D level and obstetric outcomes.